Cystatin-like protein of sweet orange (CsinCPI-2) modulates pre-osteoblast differentiation via β-Catenin involvement - da Costa Fernandes, Célio [UNESP] (2021)
Phytocystatins are endogenous cysteine-protease inhibitors present in plants. They are involved in initial germination rates and in plant defense mechanisms against phytopathogens. Recently, a new phytocystatin derived from sweet orange, CsinCPI-2, has been shown to inhibit the enzymatic activity of human cathepsins, presenting anti-inflammatory potential and pro-osteogenic effect in human dental pulp cells. The osteogenic potential of the CsinCPI-2 protein represents a new insight into plants cysteine proteases inhibitors and this effect needs to be better addressed. The aim of this study was to investigate the performance of pre-osteoblasts in response to CsinCPI-2, mainly focusing on cell adhesion, proliferation and differentiation mechanisms. Together our data show that in the first hours of treatment, protein in CsinCPI-2 promotes an increase in the expression of adhesion markers, which decrease after 24 h, leading to the activation of Kinase-dependent cyclines (CDKs) modulating the transition from G1 to S phases cell cycle. In addition, we saw that the increase in ERK may be associated with activation of the differentiation profile, also observed with an increase in the B-Catenin pathway and an increase in the expression of Runx2 in the group that received the treatment with CsinCPI-2. [Figure not available: see fulltext.].